Genocide culture - Sałiḧ, Kazîwe, author. Link
1 online resource.
Keywords: "This book considers different stages of Kurdish history, oppression, and genocide, through a critical lens offering an historiography of Iraq and of colonialism. Divided into two parts, the first part conceptualizes the term 'genocide culture' and examines dominant Iraqi cultural practices which fostered genocide. The second contextualizes the experiences of the Kurdish community to examine the effects of the cultural practices and the role of "civilian actors" in fuelling the extermination of targeted groups"--